Suitability of soccer training drills for endurance training - Little, T.; Williams, A. G. (The Journal of Strength and Conditioning Research, 2006)
Recent evidence suggests that certain soccer drills produce exercise intensities suitable for physical conditioning. However, it remains debatable whether soccer drills can provide a sufficiently unified exercise intensity among different players and on repetition of a drill, because movement patterns cannot be externally controlled during soccer drills. Good reliability and low variability of exercise intensity would enable all players to receive an appropriate training stimulus. The purpose of this study was to investigate intersubject variability and intrasubject reliability in exercise intensity during soccer drills. It was hypothesized that soccer drills that involve the highest exercise intensities would demonstrate the lowest intersubject variability and the highest intrasubject reliability. Heart rates of 23 professional soccer players were recorded during a range of soccer training drills. The drills consisted of 2 vs. 2 to 8 vs. 8 normal scoring games and 2 further possession games. Heart rate responses were examined for variability, reliability, and suitability for soccer endurance training. Coefficients of variation across players were less than 3% for all drills. Paired t-tests showed no significant differences in heart rate on repetition of the drills and 95% ratio limits of agreement were 1.8-3.8%. There were no significant correlations between exercise intensity and the statistical measures of variability and reliability. Several drills produced exercise intensities suitable for soccer endurance training with mean heart rate responses ranging from 87-91% HRmax. Soccer drills such as those used in the present study appear to be an adequate substitute for physical training without the ball and thus provide simultaneous skill and fitness training. The increase in training time spent developing technical ability and/or a reduction in total training time required may be useful for soccer teams.